Show that:
$(i)$ $\tan 48^{\circ} \tan 23^{\circ} \tan 42^{\circ} \tan 67^{\circ}=1$
$(ii)$ $\cos 38^{\circ} \cos 52^{\circ}-\sin 38^{\circ} \sin 52^{\circ}=0$
(i) $\tan 48^{\circ} \tan 23^{\circ} \tan 42^{\circ} \tan 67^{\circ}$
$=\tan \left(90^{\circ}-42^{\circ}\right) \tan \left(90^{\circ}-67^{\circ}\right) \tan 42^{\circ} \tan 67^{\circ}$
$=\cot 42^{*} \cot 67^{*} \tan 42^{*} \tan 67^{\circ}$
$=\left(\cot 42^{\circ} \tan 42^{\circ}\right)\left(\cot 67^{*} \tan 67^{\circ}\right)$
$=(1)(1)$
$=1$
(ii) $\cos 38^{\circ} \cos 52^{\circ}-\sin 38^{\circ} \sin 52^{\circ}$
$=\cos \left(90^{\circ}-52^{\circ}\right) \cos \left(90^{\circ}-38^{\circ}\right)-\sin 38^{\circ} \sin 52^{\circ}$
$=\sin 52^{*} \sin 38^{\circ}-\sin 38^{\circ} \sin 52^{*}$
$=0$
Evaluate the following:
$\frac{\sin 30^{\circ}+\tan 45^{\circ}-\operatorname{cosec} 60^{\circ}}{\sec 30^{\circ}+\cos 60^{\circ}+\cot 45^{\circ}}$
Evaluate:
$\operatorname{cosec} 31^{\circ}-\sec 59^{\circ}$
Given $\tan A=\frac{4}{3},$ find the other trigonometric ratios of the $\angle A$
$\frac{2 \tan 30^{\circ}}{1+\tan ^{2} 30^{\circ}}=$
$\frac{1-\tan ^{2} 45^{\circ}}{1+\tan ^{2} 45^{\circ}}=$